2015
DOI: 10.1074/jbc.m114.634527
|View full text |Cite
|
Sign up to set email alerts
|

ADP-ribosylation Factor 6 (ARF6) Bidirectionally Regulates Dendritic Spine Formation Depending on Neuronal Maturation and Activity

Abstract: Background:Conflicting results regarding the role of ARF6 in dendritic spine development have not been answered. Results: ARF6-mediated Rac1 or RhoA activation via PLD pathway either positively or negatively regulates spine formation. Conclusion:The key factor underlying conversion of the ARF6 effect during development is neuronal activity. Significance: Activity dependence of ARF6-mediated spine formation may play a role in structural plasticity of mature neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 52 publications
1
43
0
Order By: Relevance
“…In young but not in mature cultures, we detected tonic GluN2B-BRAG1 signaling that may contribute to the Arf6-dependent morphological maturation of dendritic spines (18,19) and/or to the relatively low plasticity threshold of young synapses (46). In mature neurons, NMDAR-depen- dent Arf6 activation relied on signaling through GluN2A and BRAG2 and was not induced by the endogenous excitation in the culture.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In young but not in mature cultures, we detected tonic GluN2B-BRAG1 signaling that may contribute to the Arf6-dependent morphological maturation of dendritic spines (18,19) and/or to the relatively low plasticity threshold of young synapses (46). In mature neurons, NMDAR-depen- dent Arf6 activation relied on signaling through GluN2A and BRAG2 and was not induced by the endogenous excitation in the culture.…”
Section: Discussionmentioning
confidence: 86%
“…Arf6 regulates membrane trafficking and actin cytoskeleton remodeling at the * This work was supported by the Deutsche Forschungsgemeinschaft (KO plasma membrane (16,17). Experiments in primary neuronal cultures indicated that Arf6 influences the maturation and maintenance of dendritic spines (18,19) and that a significant fraction of AMPARs recycles through Arf6-positive endosomes (20).…”
mentioning
confidence: 99%
“…Arf6 is a small GTPase that regulates a variety of neuronal functions, including neuronal migration (Falace et al, 2014), the formation of axons (Hernández-Deviez et al, 2002), dendrites, and spines (Miyazaki et al, 2005; Raemaekers et al, 2012; Kim et al, 2015), and synaptic plasticity (Scholz et al, 2010) through the endosomal trafficking and actin cytoskeleton reorganization. In this study, we provide evidence suggesting that the Arf6-FIP3 pathway regulates neuronal migration in the IZ through the endosomal trafficking of N-cadherin.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of small G proteins can be regulated by different mechanisms such as posttranslational modifications, guanine nucleotide exchange factors (GEFs), GTPase activating proteins (GAPs) and guanine nucleotide dissociation inhibitors (GDIs) [15][16][17][18][19][20][21]. The Rho GTPase-activating proteins are one of the major classes of regulators found in all eukaryotes, which are crucial in cell cytoskeletal organization [22][23][24][25][26], cycle [27][28][29][30][31], proliferation [32][33][34][35][36][37][38], differentiation [39][40][41], neuronal development [42][43][44][45][46][47] and synaptic functions [48][49][50]. But Rho-family GAPs are more numerous than the GTPases themselves and typically contain interaction domains through which they are directed to specific subcellular compartments and might recruit upstream regulators, downstream effectors and cytoplasmic scaffolds.…”
Section: Discussionmentioning
confidence: 99%